KAJIAN PENERAPAN ANGKUTAN UMUM PERKOTAAN TANPA BAYAR - Basuki, Imam; Susanto, Benidiktus (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
For reduce urban congestion by reasing the use of urban public transport so that the use of private transport is reduced. The studied urban public transport services without pay as an alternative solution to avoid congestion in urban areas . Studies conducted by the Focus Group Discussion of various urban transport stakeholders. The results showed that brainstorming operational funding of urban public transport as an alternative source of financing depends on the policy of the government. The government should give priority to the use of public transport than private transport. A variety of alternative sources of income can be taken from vehicle tax, road pricing , utilization and vehicle stops to billboards and so forth. The final choice is the presence of government subsidies. If not allow the application of transport without pay made ​​efforts to provide discounts for certain groups at certain times.